2017
DOI: 10.1016/j.celrep.2016.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Human Carboxylesterase 2 Reverses Obesity-Induced Diacylglycerol Accumulation and Glucose Intolerance

Abstract: SummarySerine hydrolases are a large family of multifunctional enzymes known to influence obesity. Here, we performed activity-based protein profiling to assess the functional level of serine hydrolases in liver biopsies from lean and obese humans in order to gain mechanistic insight into the pathophysiology of metabolic disease. We identified reduced hepatic activity of carboxylesterase 2 (CES2) and arylacetamide deacetylase (AADAC) in human obesity. In primary human hepatocytes, CES2 knockdown impaired gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 48 publications
1
88
1
Order By: Relevance
“…Body weight and body mass composition of Ces2c int mice were comparable to controls on chow. However, on HFD, Ces2c int mice were protected from diet‐induced obesity and liver steatosis, highlighting an important function of Ces2c in the small intestine during metabolic stress, as suggested for hepatic Ces2c / CES2 . In line with the aforementioned studies exploring hepatic Ces2c function, we add additional insights into the importance of Ces2c to efficiently hydrolyze TGs and DGs, thereby generating 2‐MGs in the small intestine.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Body weight and body mass composition of Ces2c int mice were comparable to controls on chow. However, on HFD, Ces2c int mice were protected from diet‐induced obesity and liver steatosis, highlighting an important function of Ces2c in the small intestine during metabolic stress, as suggested for hepatic Ces2c / CES2 . In line with the aforementioned studies exploring hepatic Ces2c function, we add additional insights into the importance of Ces2c to efficiently hydrolyze TGs and DGs, thereby generating 2‐MGs in the small intestine.…”
Section: Discussionsupporting
confidence: 77%
“…C), which are typical esterase substrates. Two studies indicated that Ces2c also harbors TGH activity; however, enzymatic activities (levels of hydrolyzed FAs per time) were not indicated. To characterize the enzymatic function of Ces2c, we measured FA release by TGH and DGH activities in cell lysates prepared from COS‐7 cells overexpressing FLAG‐tagged Ces2c as described .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has become a major public health problem worldwide, and its prevalence has dramatically increased over several decades . Furthermore, it is associated with other diseases such as nonalcoholic fatty liver, type 2 diabetes, hypertension, coronary artery disease, and various forms of cancer . A growing body of evidence has shown that gut microbiota plays a critical role in nutrient acquisition, energy harvest, and lipid metabolism, which may contribute to the metabolic diseases .…”
Section: Introductionmentioning
confidence: 99%